Alcohol Vapor Inhalation as a Model of Alcohol‐Induced Organ Disease. (4th July 2016) - Mouton, Alan J.; Maxi, John K.; Souza‐Smith, Flavia; Bagby, Gregory J.; Gilpin, Nicholas W.; Molina, Patricia E.; Gardner, Jason D.
Abstract : Background: Chronic intermittent ethanol vapor (CIEV) exposure has been used extensively to produce rodent models of alcohol dependence, but unlike other models of alcohol abuse, CIEV has not been assessed as a model of end‐organ damage. The purpose of this study was to characterize the effects of CIEV on peripheral organ systems affected by alcohol abuse, including the liver, lungs, and cardiovascular system. Methods: Adult male Sprague‐Dawley rats were exposed to daily CIEV for a period of 8 weeks (14HR ON/10HR OFF), producing blood alcohol levels of 200 mg/dl. Controls were exposed to room air. After 8 weeks, echocardiography was performed to assess cardiac function. Indices of liver injury (alanine and aspartate aminotransferases [ALT and AST]; cytochrome p450 2E1 [CYP2E1]; alcohol dehydrogenase [ADH]; Oil Red O and triglyceride content; lipid peroxidation; inflammatory cytokine expression; and macrophage infiltration), and lung inflammatory cell count, proinflammatory cytokine expression, and lipid peroxidation were measured. Results: Left ventricular posterior wall thickness was significantly decreased, and systolic blood pressure was significantly elevated by CIEV compared with air controls. CIEV led to a significant increase in plasma ALT and triglycerides compared with room air controls. CIEV did not affect liver triglyceride content, lipid staining or peroxidation, but increased CYP2E1 and chemokine (C‐C motif) ligand 2 (CCL2) protein expression, while decreasing ADH expression. CIEV significantly increased numbers of both polymorphonuclear neutrophils and lymphocytes in the bronchoalveolar lavage fluid, indicative of pulmonary inflammation. However, CIEV did not produce significant changes in lung mass, pulmonary lipid peroxidation, inflammatory cytokine expression, or edema. Conclusions: These results show that CIEV produces hepatic, pulmonary, and cardiovascular effects in rats similar to those found in other models of chronic alcohol administration. Alcohol vapor administration is a novel method of alcohol‐induced tissue injury with high potential for widespread use in alcohol toxicology research. Abstract : Sprague–Dawley rats were exposed to chronic intermittent ethanol vapor (CIEV) inhalation, which has previously been used exclusively for neurobehavioral and addiction studies. CIEV led to pathological changes commonly observed in alcohol‐induced liver injury, including increased plasma ALT (A) and triglycerides (C). CIEV also altered hepatic alcohol‐metabolizing enzymes, including increased Cyp2e1 (D) and decreased ADH (E). These data suggest that CIEV is a potential preclinical alternative to standard ingestion models for studying the biomedical consequences of chronic alcohol abuse.